2021
DOI: 10.1177/0300060521989893
|View full text |Cite
|
Sign up to set email alerts
|

Performance of TDR-300B and VITEK®2 for the identification of Pseudomonas aeruginosa in comparison with VITEK®-MS

Abstract: Objective Automated systems are needed for the rapid and accurate diagnosis of Pseudomonas-associated nosocomial infections among critically ill patients admitted to the intensive care unit. We assessed the performance of TDR-300B and VITEK®2 for the identification of P. aeruginosa using VITEK®-MS as the gold standard. Methods This analytical study employed a cross-sectional approach. First, 44 clinical isolates of P. aeruginosa were collected and refreshed. Next, a single colony of oxidase-positive, gram-nega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…Vitek 2 ® system is among the most recent reliable techniques for identifying pathogenic bacteria [36]. Vitek 2 ® system is the gold standard for P. aeruginosa identification with 100% accuracy, as described by Moehario et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Vitek 2 ® system is among the most recent reliable techniques for identifying pathogenic bacteria [36]. Vitek 2 ® system is the gold standard for P. aeruginosa identification with 100% accuracy, as described by Moehario et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its easy application, time- and cost-effectiveness, the VITEK ® 2 system is being increasingly used in everyday practice [ 50 ]. This system efficiently identifies Staphylococci species, MRS, and other bacterial species [ 33 , 51 53 ]. In our study, the Kappa analysis showed almost perfect agreement between the VITEK ® 2 system and molecular methods for overall identification.…”
Section: Discussionmentioning
confidence: 99%
“…Для идентификации бактериальных изолятов до уровня видов использовали автоматический бактериологический анализатор VITEK® 2 («bio-Merieux SA», Франция) и систему MALDI-TOF MS («bioMerieux SA», Франция) в соответствии с описаниями (14,15). Отдельные колонии отбирали на скошенном агаре и суспендировали в 2,5 мл 0,45 % стерильного физиологического раствора, доводя бактериальную суспензию до стандарта мутности МакФарланда 0,5 с помощью денситометра («bioMerieux SA», Франция) в соответствии с инструкциями производителя.…”
unclassified
“…Бактериальные взвеси готовили в течение 30 мин после внесения в кассету для идентификации грамотрицательных (GN) бактерий с использованием автоматического анализатора VITEK® 2. Анализ проводили с помощью программы VITEK® 2 v. 07.01 («bioMerieux SA», Франция) (15), вероятность выше 80 % при соответствующем профиле считали достаточной при идентификации в пределах перечня микроорганизмов, определяемых до видов или родов (таксонов) с помощью VITEK® 2 (14,15).…”
unclassified
See 1 more Smart Citation